Remote Control System For Multi Mobile Robot Using A Combination of Computer-Microcontroller - Nanang Ismail; Okyza MP; Dimas Widyasastrena (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
Various control systems have been used to optimizerobot performance, one of them is to utilize radio wave. The use ofradio wave is very common because they are cheap and easy todeploy. Radio frequency use is also various; some use VHF, someothers UHF for many purposes. One control system for one robot isdefinitely inefficient, therefore a continuous research on robotcontrol system is required to control multi robots with differentradio frequencies using one control system. This research is meantto develop multiple mobile robots using 40 MHz and 315 MHzfrequency within one system controlled by integrated computer andmicrocontroller. The frequency selection represents VHF and UHFfrequency. This research is a prototype for multi robot control.Testing is done with several methods; system interface testing, Lineof Sight robot control system, and robot control system in anobscured environment. System interface testing is done by usingserial port communication to communicate computer with 8-bitmicrocontroller using ASCII. Line of Sight testing exerts maximumrange of 4 meters using 40 MHz, and 10 meters using 315 MHz.Obscured environment testing exerts maximum range of 2.8 metersfor 40 MHz and 13.4 meters for 315 MHz.